Effects of dissipative hydrodynamics on elliptic flow and HBT interferometry in central collisions at RHIC - Lemos, D. S. [UNESP]; Socolowski, O. Jr Jr; Guimaraes, V; Genezini, F.; Lubian, J.; Assuncao, M.; Delgado, A.; Trevisan, L. A. (Iop Publishing Ltd, 2019)
In this work, we study relativistic heavy ion collisions by using a hydrodynamic model for both ideal and viscous cases to investigate the influence of dissipative effects on the elliptic flow and HBT interferometry. We conclude that the bulk viscosity has small influence in hydrodynamic calculations. However, our results show that the shear effects are important for describing the experimental data in central collisions.